Potential Roles of Hypoxia-Inducible Factor-1 in Alzheimer's Disease: Beneficial or Detrimental? - Tsu-Kung Lin; Chi-Ren Huang; Kai-Jung Lin; Yi-Heng Hsieh; Shang-Der Chen; Yi-Chun Lin; A-Ching Chao; Ding-I Yang (MDPI AG, 2024)
The major pathological characteristics of Alzheimer's disease (AD) include senile plaques and neurofibrillary tangles (NFTs), which are mainly composed of aggregated amyloid-beta (Aβ) peptide and hyperphosphorylated tau protein, respectively. The excessive production of reactive oxygen species (ROS) and neuroinflammation are crucial contributing factors to the pathological mechanisms of AD. Hypoxia-inducible factor-1 (HIF-1) is a transcription factor critical for tissue adaption to low-oxygen tension. Growing evidence has suggested HIF-1 as a potential therapeutic target for AD; conversely, other experimental findings indicate that HIF-1 induction contributes to AD pathogenesis. These previous findings thus point to the complex, even contradictory, roles of HIF-1 in AD. In this review, we first introduce the general pathogenic mechanisms of AD as well as the potential pathophysiological roles of HIF-1 in cancer, immunity, and oxidative stress. Based on current experimental evidence in the literature, we then discuss the possible beneficial as well as detrimental mechanisms of HIF-1 in AD; these sections also include the summaries of multiple chemical reagents and proteins that have been shown to exert beneficial effects in AD via either the induction or inhibition of HIF-1.